Pengaruh Karakteristik Perusahaan Terhadap Waktu Penyelesaian Audit (Timeliness)(Studi Kasus Pada Perusahaan Manufaktur Subsektor Otomotif yang Terdaftar di BEI Periode 2010-2014) - Mulyono, Budi; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2017)
This study aimed to examine the effect of firm size, solvency, profit / loss of the company, leverage, and firm size to audit completion time (timeliness). The population in this study is a subsector of automotive manufacturing companies listed in Indonesia Stock Exchange 2010-2014. Samples were selected using purposive sampling method, ie a total of 18 companies. The analysis method used The analysis method used is multiple regression analysis. The results showed that the variable leverage as measured by the DER and firm size as measured by a dummy variable affects the timeliness, while the size of the company measured by ln (total assets), solvency as measured by DTA, and the profit / loss of the company as measured by the dummy is not effect on timeliness.